Resíduo de goiaba: metabolismo em ratos e aplicabilidade em barras de cereais - Roberto, Bruna Sampaio (2012)
During the agroindustrial processing steps of guava, are wasted materials such as peel and seed that are considered waste. However, waste represent considerable volumes of alternative sources of nutrients for human nutrition and that are discarded. In this context, this study aimed to determine the composition, physico-chemical and technological properties of the residue of guava, peel and seed, as well as evaluate the effect of diets prepared with this residue as a source of fiber parameters on biological response in Wistar rats. Additionally, cereal bars were developed, using seed meal and peel meal of guava as source of dietary fiber. The residues were analyzed for dry-matter content, ash, protein, lipids, dietary fiber, pectin, phenolic compounds, the copper binding capacity, hidration capacity, syneresis and fat binding capacity. The biological assay was conducted using 40 male Wistar rats, divided into four treatments of 10 animals, with different dietary fiber source: CONT, feed with AIN93G, TC, feed with guava peel, TS, feed with guava seed, TCS, feed with peel and seeds of guava. Later, cereal bars with high fiber content were developed, which were evaluated sensorially and nutritionally by chemical composition. The results showed the peel is a material rich in dietary fiber, highlighting the high content of soluble fiber and pectin. The guava peel is natural source of energy and minerals, with high hydration capacity and low syneresis. The seed showed good yield as a source of fiber, especially insoluble, protein and oil. Peel and seed showed significant value of copper binding capacity and phenolic compounds. Peel and seeds of guava as fiber source in diets of rats did not affect weight gain, average feed intake, feed conversion, epididymal fat, weight of liver and pancreas, total cholesterol, glucose and total protein. The animals submitted to treatment only with peel fibers had higher digestibility, higher content of nitrogen in the faeces, greater weight of the intestine and HDL increased. Treatment only with seed as fiber source allowed shortest time of transit. Regardless of the proportion of peel in the diet, the faces pH waslower. The decrease of triglycerides was greater when seed was introduced into the diet. The formulations of cereal bars tested had an average of 10,93% moisture, 60,55% of total carbohydrates, 9,62% lipids, 8,41% protein, 1,38% ash and 20,02% dietary fiber, increasing the fiber content in relation to the standard formulation. The test formulations showed satisfactory acceptability in all sensory attributes. Was not observed preference by formulation or significant influence of the proportion of waste, except for the texture, for the which the formulation with the highest percentage of waste had the smaller values. The study showed that peel and seeds of guava, usually wasted, have wide applicability in the food industry, being materials nutritious and source of fiber, which can assist be alternatives in order to control of biochemical parameters relevant. The formulations of cereal bar containing peel and seed of guava are source of fiber, consistent with the requirements of today's consumers who want products with nutritional and sensory quality.